A low-cost uniaxial cell stretcher for six parallel wells - Kah, Delf-Thorge Eric; Winterl, Alexander; Přechová, Magdalena; Schöler, Ulrike; Schneider, Werner; Friedrich, Oliver; Gregor, Martin; Fabry, Ben (HardwareX, 2021)
Cells in the lungs, the heart, and numerous other organs, are constantly exposed to dynamic forces and deformations. To mimic these dynamic mechanical loading conditions and to study the resulting cellular responses such as morphological changes or the activation of biochemical signaling pathways, cells are typically seeded on flexible 2D substrates that are uniaxially or biaxially stretched. Here, we present an open-source cell stretcher built from parts of an Anet A8 3D printer. The cell stretcher is controlled by a fully programmable open-source software using GCode and Python. Up to six flexible optically clear substrates can be stretched simultaneously, allowing for comparative multi-batch biological studies including microscopic image analysis. The cell yield from the cell culture area of 4 cm2 per substrate is sufficient for Western-blot protein analysis. As a proof-of-concept, we study the activation of the Yes-associated protein (YAP) mechanotransduction pathway in response to increased cytoskeletal tension induced by uniaxial stretching of epithelial cells. Our data support the previously observed activation of the YAP transcription pathway by stretch-induced increase in cytoskeletal tension and demonstrate the suitability of the cell stretcher to study complex mechano-biological processes.
CRIS-Team Scopus Importer:2021-01-01
Keywords: 3D printer; Cell Mechanics; Cell stretcher; Mechanosensing; Uniaxial stretch; YAP

A novel modular opto-biomechatronics bioreactor for simultaneous isotropic mechanical stretch application and fluorescence microscopy under cell and tissue culture conditions - Merten, Anna-Lena; Schöler, Ulrike; Lesko, Christian; Kreiß, Lucas; Schneidereit, Dominik; Linsenmeier, Fabian; Stolz, Axel; Rappl, Sebastian; Ali, Mohamed; Potié, Tim; Ahmed, Adel; Morales-Dalmau, Jordi; et al. (Biosensors and Bioelectronics: X, 2024)
Mechanical stresses are an environmental challenge virtually all tissues in the body are exposed to and thus, are of fundamental interest to study cell reactions in mechanobiology. Yet, unlike acute short-term mechanical cell stimulations, long-term or cyclic mechano-stimulation as experienced in the body is difficult to reproduce. Bioreactors are designed to control cell culture conditions, but still, there are yet no technical solutions available to merge bioreactor and opto-biomechatronics technologies for cyclic stretch-applications and simultaneous live cell imaging. To close this gap, we have engineered an opto-biomechatronics module, consisting of our in-house developed IsoStretcher technology and customised epifluorescence optics, into an automated bioreactor platform. For this, redesigned polydimethylsiloxane (PDMS) chambers with closed geometry (∽700 μL internal volume) to warrant sterile operation were developed. Those chambers could be flushed with cell solution for cell seeding in a sterile manner. The epifluorescence imaging module was engineered into the reactor underneath the IsoStretcher to allow for continuous image acquisition during long-term stretch cycles (hours to days). The system was validated on human fibroblast BJ foreskin cells, and Cal-520 Ca2＋ fluorescence was stably imaged using our in-built autofocus functionality. Cultures for 24 h within the IsoStretcher-bioreactor preserved a normal cell morphology as compared to external incubator control cultures. Isotropic stretch was reliably transferred to the cell membranes. Our system with in-built bioreactor and opto-biomechatronics functionality provides a holistic technology platform for the growing field of mechanobiology to allow long-term observations of cultured single cells and confluent cell layers that are subjected to cyclic long-term isotropic stretch protocols.
CRIS-Team Scopus Importer:2024-01-19
Keywords: Automation; Bioreactor; Cell stretching device; Mechanosensitive ion channels; Mechanotransduction

High-content method for mechanosignaling studies using IsoStretcher technology and quantitative Ca2+ imaging applied to Piezo1 in cardiac HL-1 cells - Merten, Anna-Lena; Schöler, Ulrike; Guo, Yang; Linsenmeier, Fabian; Martinac, Boris; Friedrich, Oliver; Schürmann, Sebastian (Cellular and Molecular Life Sciences, 2024)
The importance of mechanosensory transduction pathways in cellular signalling has prominently come to focus in the last decade with the discovery of the Piezo ion channel family. Mechanosignaling involving Piezo1 ion channels in the function of the heart and cardiovascular system has only recently been identified to have implications for cardiovascular physiology and pathophysiology, in particular for heart failure (i.e., hypertrophy or dilative cardiomyopathy). These results have emphasized the need for higher throughput methods to study single-cell cardiovascular mechanobiology with the aim of identifying new targets for therapeutic interventions and stimulating the development of new pharmacological agents. Here, we present a novel method to assess mechanosignaling in adherent cardiac cells (murine HL-1 cell line) using a combination of isotropic cell stretch application and simultaneous Ca2+ fluorescence readout with quantitative analysis. The procedure implements our IsoStretcher technology in conjunction with a single-cell- and population-based analysis of Ca2+ signalling by means of automated image registration, cell segmentation and analysis, followed by automated classification of single-cell responses. The method is particularly valuable for assessing the heterogeneity of populations with distinct cellular responses to mechanical stimulation and provides more user-independent unbiased drug response classifications.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Cardiomyocytes; Cell stretching; GsMTx4; Mechanobiology; Mechanosensitive; Mechanotransduction; Yoda1

In vitro cell stretching technology (IsoStretcher) as an approach to unravel Piezo1-mediated cardiac mechanotransduction - Guo, Yang; Merten, Anna-Lena; Schöler, Ulrike; Yu, Ze Yan; Cvetkovska, Jasmina; Fatkin, Diane; Feneley, Michael P.; Martinac, Boris; Friedrich, Oliver (Progress in Biophysics & Molecular Biology, 2021)
The transformation of electrical signals into mechanical action of the heart underlying blood circulation results in mechanical stimuli during active contraction or passive filling distention, which conversely modulate electrical signals. This feedback mechanism is known as cardiac mechano-electric coupling (MEC). The cardiac MEC involves complex activation of mechanical biosensors initiating short-term and long-term effects through Ca2+ signals in cardiomyocytes in acute and chronic pressure overload scenarios (e.g. cardiac hypertrophy). Although it is largely still unknown how mechanical forces alter cardiac function at the molecular level, mechanosensitive channels, including the recently discovered family of Piezo channels, have been thought to play a major role in the cardiac MEC and are also suspected to contribute to development of cardiac hypertrophy and heart failure. The earliest reports of mechanosensitive channel activity recognized that their gating could be controlled by membrane stretch. In this article, we provide an overview of the stretch devices, which have been employed for studies of the effects of mechanical stimuli on muscle and heart cells. We also describe novel experiments examining the activity of Piezo1 channels under multiaxial stretch applied using polydimethylsiloxane (PDMS) stretch chambers and IsoStretcher technology to achieve isotropic stretching stimulation to cultured HL-1 cardiac muscle cells which express an appreciable amount of Piezo1.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Cell stretching device; HL-1; Mechanosensitive ion channel; Mechanotransduction; Piezo1; Polydimethylsiloxane (PDMS)

Quantitative Live-Cell Ca2+ Imaging During Isotropic Cell Stretch - Schöler, Ulrike; Merten, Anna-Lena; Schürmann, Sebastian; Friedrich, Oliver (Cell Viability Assays (2nd Edt), 2023)
Cell viability of many cell types strongly relies on their ability to adjust to mechanical conditions and alterations. Cellular mechanisms for sensing and responding to mechanical forces and pathophysiological variations in these processes have become an emerging research field in recent years. An important signaling molecule involved in mechanotransduction as in many cellular processes is Ca2+. New experimental methods to probe cellular Ca2+ signaling live under conditions of mechanical stimulation facilitate new insights into previously overlooked aspects of mechanical regulation of cells. Here, we describe a protocol for using Ca2+ imaging in combination with a cell stretching device, the IsoStretcher. Cells grown on elastic membranes can be isotopically stretched in-plane, and their intracellular Ca2+ level can be accessed online on the single cell level using fluorescent calcium indicator dyes. We show a protocol for functional screening of mechanosensitive ion channels and related drug screenings using BJ cells, a foreskin fibroblast cell line that strongly reacts to acute mechanical stimulation.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Calcium imaging; Cell stretching; Image processing; IsoStretcher; Mechanobiology; Mechanosignaling; Mechanotransduction